Perspective of Inflammation and Inflammation Markers - Nnodim Johnkennedy; Okafor Chibuzor Mercy (Journal La Medihealtico, 2022)
Progression and occurrence of coronary heart disease can be attributed in part to the presence of inflammation. As a result of our understanding of inflammation's molecular underpinnings, we have identified markers that may also serve as new treatment targets for atherosclerosis. Individuals with and without a history of cardiovascular disease can benefit from monitoring their C-reactive protein (CRP) levels (CVD). The anti-inflammatory characteristics of statins have lately been explored, and they have been shown to significantly lower cardiovascular morbidity and death. C-reactive protein, adiponectin, CD40 ligand, and lipoprotein-associated phospholipase A were the focus of this review, which also looked at statins' effect on these biomarkers and their potential link to cardiovascular events, all of which are thought to be involved in the inflammatory process that leads to atherothrombosis and other cardiovascular diseases.